2014
DOI: 10.1002/ps.3872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insecticidal fusion proteins containing spider toxins targeting sodium and calcium ion channels on pyrethroid‐resistant strains of peach‐potato aphid (Myzus persicae)

Abstract: Mutations in the sodium channel in pyrethroid-resistant aphids also protect against a fusion protein containing a sodium-channel-specific toxin, in spite of differences in ligand-channel interactions, but do not confer resistance to a fusion protein targeting calcium channels. The use of fusion proteins with differing targets could play a role in managing pesticide resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Secreted proteins were separated from cells by centrifugation (30 min at 7500 g, 4 °C) and clarified by vacuum filtration through 2.7 and 0.7 µM glass fibre filters (Whatman). Recombinant proteins were purified from supernatants by nickel affinity chromatography, dialysed and freeze-dried as described previously (Yang et al 2014). Protein contents in lyophilized samples were determined from SDS-PAGE gels stained for total proteins with coomassie blue.…”
Section: Recombinant Protein Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secreted proteins were separated from cells by centrifugation (30 min at 7500 g, 4 °C) and clarified by vacuum filtration through 2.7 and 0.7 µM glass fibre filters (Whatman). Recombinant proteins were purified from supernatants by nickel affinity chromatography, dialysed and freeze-dried as described previously (Yang et al 2014). Protein contents in lyophilized samples were determined from SDS-PAGE gels stained for total proteins with coomassie blue.…”
Section: Recombinant Protein Productionmentioning
confidence: 99%
“…We have previously demonstrated that linkage of Hv1a to GNA greatly enhances the oral efficacy of the neurotoxin by virtue of the stability of GNA to gut proteolysis, and its ability to cross the gut epithelium and deliver Hv1a to the circulatory system, in larvae of the Lepidopteran Mamestra brassicae (Fitches et al 2012). Fusion to GNA has similarly been used to enhance oral efficacy of the venom toxins SFI1 (Segestria florentina toxin 1), PI1a (δ-Amaurobitoxin from Pireneitega luctuosus) and ButaIT (Red Scorpion toxin from Buthus tamulus) towards a range of insects (Fitches et al 2004(Fitches et al , 2010Yang et al 2014;Trung et al 2006). Analogously, a luteovirus coat protein has been successfully used as a carrier to greatly enhance the oral toxicity of Hv1a to a range of aphid pest species (Bonning et al 2014).…”
mentioning
confidence: 99%
“…Fortunately, the potential toxicity of HtA against vertebrates can be overcome by the design of new variants, such as those involving Trp mutations [ 35 ]. Protein fusions can also enhance insecticidal activity or alter the insecticidal pathway [ 36 , 37 ]. Therefore, HtA might be a candidate for genetic engineering and may fuse with other insecticidal proteins, such as snowdrop lectin, specific insect neurotoxins (from spider, scorpion or other poisonous animals) or Cry toxin from Bacillus thuringiensis , to enhance its insecticidal activity or change its insecticidal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Most peptide toxins acting on insect Na V s were gating modifiers, whose binding sites in insect Na V s were distinct from chemical insecticides such as DDT, DDT analogues, and pyrethroids [ 10 ]. Thus they might be promising bioinsecticide candidates in terms of managing pests carrying chemical insecticide-resistant Na V s mutations, as a previous study showed a spider toxin was active on pyrethroid-resistant strains of peach-potato aphid although the potency was slightly compromised [ 11 ]. It is possible to develop insecticides which discriminate pests from beneficial insects by using insect Na V s as molecular targets, as inspired by the observation that spider toxins β-Diguetoxin-Dc1a and µ-theraphotoxin-Ae1a even showed selectivity between the highly conserved PaNa V 1 and BgNa V 1 channels from two cockroach species [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%